A deep intronic CLRN1 (USH3A) founder mutation generates an aberrant exon and underlies severe Usher syndrome on the Arabian Peninsula - Arif O. Khan (Nature Portfolio, 2017)
Abstract Deafblindness is mostly due to Usher syndrome caused by recessive mutations in the known genes. Mutation-negative patients therefore either have distinct diseases, mutations in yet unknown Usher genes or in extra-exonic parts of the known genes – to date a largely unexplored possibility. In a consanguineous Saudi family segregating Usher syndrome type 1 (USH1), NGS of genes for Usher syndrome, deafness and retinal dystrophy and subsequent whole-exome sequencing each failed to identify a mutation. Genome-wide linkage analysis revealed two small candidate regions on chromosome 3, one containing the USH3A gene CLRN1, which has never been associated with Usher syndrome in Saudi Arabia. Whole-genome sequencing (WGS) identified a homozygous deep intronic mutation, c.254–649T > G, predicted to generate a novel donor splice site. CLRN1 minigene-based analysis confirmed the splicing of an aberrant exon due to usage of this novel motif, resulting in a frameshift and a premature termination codon. We identified this mutation in an additional two of seven unrelated mutation-negative Saudi USH1 patients. Locus-specific markers indicated that c.254–649T > G CLRN1 represents a founder allele that may significantly contribute to deafblindness in this population. Our finding underlines the potential of WGS to uncover atypically localized, hidden mutations in patients who lack exonic mutations in the known disease genes.